Temporal pole signal abnormality on MR imaging in temporal lobe epilepsy with hippocampal sclerosis: a fluid-attenuated inversion-recovery study Anormalidade de sinal na imagem por RM do pólo temporal na epilepsia do lobo temporal com esclerose hipocampal: um estudo pela seqüência inversão recuperação com supressão da água livre (FLAIR) - Henrique Carrete Junior; Nitamar Abdala; Kátia Lin; Luís Otávio Caboclo; Ricardo Silva Centeno; Américo Ceiki Sakamoto; Jacob Szjenfeld; Roberto Gomes Nogueira; Elza Márcia Targas Yacubian (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the frequency and regional involvement of temporal pole signal abnormality (TPA) in patients with hippocampal sclerosis (HS) using fluid-attenuated inversion-recovery (FLAIR) MR imaging, and to correlate this feature with history. METHOD: Coronal FLAIR images of the temporal pole were assessed in 120 patients with HS and in 30 normal subjects, to evaluate gray-white matter demarcation. RESULTS: Ninety (75%) of 120 patients had associated TPA. The HS side made difference regarding the presence of TPA, with a left side prevalence (p=0.04, chi2 test). The anteromedial zone of temporal pole was affected in 27 (30%) out of 90 patients. In 63 (70%) patients the lateral zone were also affected. Patients with TPA were younger at seizure onset (p=0.018), but without association with duration of epilepsy. CONCLUSION: Our FLAIR study show temporal pole signal abnormality in 3/4 of patients with HS, mainly seen on the anteromedial region, with a larger prevalence when the left hippocampus was involved. OBJETIVO: Determinar a freqüência e o envolvimento regional da anormalidade de sinal do pólo temporal (APT) em pacientes com esclerose hipocampal (EH) utilizando seqüência inversão recuperação com supressão da água (FLAIR) por RM, e correlacioná-la com a história. MÉTODO: Foram analisadas as imagens coronais FLAIR dos pólos temporais de 120 pacientes com EH e de 30 indivíduos normais, para avaliar a demarcação entre substâncias branca e cinzenta. RESULTADOS: Noventa (75%) dos 120 pacientes tinham APT associada. Houve prevalência do lado esquerdo (p=0.04, chi2 teste) na relação entre APT e o lado da EH. A zona ântero-medial estava acometida em 27 (30%) destes pacientes. Em 63 (70%) pacientes também a zona lateral estava acometida. Pacientes com APT apresentaram início da epilepsia quando mais jovens (p=0.018), porém sem associação com a sua duração. CONCLUSÃO: A seqüência FLAIR mostra haver ATP em 3/4 dos pacientes com EH, principalmente na região ântero-medial, com maior prevalência quando o hipocampo esquerdo estava envolvido.